2020
DOI: 10.1088/1757-899x/840/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Thermal Behaviour of Epoxy/Hexagonal Boron Nitride/Short Sisal Fiber Hybrid Composites

Abstract: Hybrid composite i.e. surface modified hexagonal boron nitride (hBN) and short sisal fiber reinforced in epoxy matrix is fabricated using hand lay-up method. The effect of surface modified hBN filler and sisal fiber content on mechanical and thermal properties of epoxy based hybrid composites were investigated in this paper. The main aim of the investigation is to develop a material which can found its application in microelectronic components. As per the requirement of microelectronic industry, the material s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The issue of heat-conducting properties of h-BN based compositions has had considerable attention in several studies [16,[18][19][20][21]24,[28][29][30][31][32][42][43][44][45][46][47]54]. Unfortunately, reported values of effective thermal conductivity were insufficient (no higher than 2.0 W•m −1 •K −1 ), since composites with relatively low-filler contents were obtained.…”
Section: Thermal Conductivity Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The issue of heat-conducting properties of h-BN based compositions has had considerable attention in several studies [16,[18][19][20][21]24,[28][29][30][31][32][42][43][44][45][46][47]54]. Unfortunately, reported values of effective thermal conductivity were insufficient (no higher than 2.0 W•m −1 •K −1 ), since composites with relatively low-filler contents were obtained.…”
Section: Thermal Conductivity Analysismentioning
confidence: 99%
“…In this respect, composites based on hexagonal boron nitride (h-BN) attract significant research interest due to their excellent dielectric properties and thermal conductivity; layered structure of h-BN provides high-and controlled property anisotropy; in addition, h-BN has superb thermal stability. The decomposition temperature of h-BN in vacuum reaches 3000 K, so respective composites are able to withstand operating temperatures limited only by decomposition temperature of the matrix material [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agarwal et al [35] fabricated surface-modified hexagonal boron nitride (hBN) and short sisal fibre reinforced in the epoxy matrix using the handlay-up method. The authors concluded that thermal conductivity increases with an increase in h-BN content.…”
Section: Introductionmentioning
confidence: 99%
“…PROPERTIESCoir fibre[27] h-BN[35] Density (g/cm 3 ) 1-2 1.9-2.0 Modulus (GPa) ii denotes the coefficient of a quadratic equation.…”
mentioning
confidence: 99%